2004
DOI: 10.3109/10606820490270870
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Modulation of Kv1.3 Channel by Two Receptor Tyrosine Kinases in Olfactory Bulb Neurons of Rodents

Abstract: Activation of the receptor tyrosine kinase (RTK), insulin (IRK) or neurotrophin B (TrkB), was characterized and compared in olfactory bulb neuron (OBN) cultures from Sprague Dawley rats and sv129 B6 mice. Current suppression attributed to modulation of the delayed rectifier, Kv1.3, a voltage-gated potassium (Kv) channel of the Shaker family, was observed following acute application of the growth factors, insulin or brain-derived neurotrophic factor (BDNF), to mitral cells of either rodent model. Using site-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…In fact, recent studies have reported that BDNF is capable of modulating the function of K channels by tyrosine phosphorylation via TrkB receptors (Tucker and Fadool, 2002). Interestingly, further study also reported that such BDNF modulation of K channels is dependent on age and previous sensory experience in the olfactory bulb (Colley et al, 2004). We have previously shown that BDNF-dependent activation of silent synapses may occur through the regulation of glutamate receptor trafficking in the thalamocortical synapses .…”
Section: What Mechanism Underlies the Impairment Of Electrophysiologimentioning
confidence: 88%
“…In fact, recent studies have reported that BDNF is capable of modulating the function of K channels by tyrosine phosphorylation via TrkB receptors (Tucker and Fadool, 2002). Interestingly, further study also reported that such BDNF modulation of K channels is dependent on age and previous sensory experience in the olfactory bulb (Colley et al, 2004). We have previously shown that BDNF-dependent activation of silent synapses may occur through the regulation of glutamate receptor trafficking in the thalamocortical synapses .…”
Section: What Mechanism Underlies the Impairment Of Electrophysiologimentioning
confidence: 88%
“…Cells were dissociated by trituration by the use of a gradedsize series of fire-polished siliconized Pasteur pipettes. In contrast to earlier studies of cultured neurons of wildtype and Kv1.3Ϫ/Ϫ animals, the cells were not plated onto a monolayer of astrocytes (Colley et al 2004;Fadool et al 2004). Instead the resulting neuron and glia suspension was plated directly onto poly-D-lysine-coated 12-mm glass coverslips and incubated in DMEM supplemented with 2% penicillin/ streptomycin and 5% FBS.…”
Section: Olfactory Bulb Primary Cell Culturementioning
confidence: 99%
“…Kv1.3, a voltage-gated potassium channel of the Shaker subfamily, is expressed at relatively high levels in olfactory bulb (OB) mitral cells, which relay signals from olfactory sensory neurons to central brain olfactory regions (Colley et al 2004). Deletion of the Kv1.3 gene in mice alters the characteristics of the outward potassium currents and changes the shape of action potentials and the firing pattern of these cells .…”
Section: Introductionmentioning
confidence: 99%
“…More studies are necessary to investigate the influence of protons and Zn 2+ on the resting membrane potential in TL and to correlate possible changes in the resting potential with TL mitogenesis. It is also known that Kv1.3 channels are present in the central nervous system, especially in olfactory bulb neurons [7][8][9], where they stabilise tonic firing of…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…These channels are expressed abundantly in human T lymphocytes (TL), where they play an important role in setting the resting membrane potential, cell mitogenesis, apoptosis and volume regulation [3][4][5][6]. Kv1.3 channels are also present in the rat central nervous system, especially in olfactory bulb neurons, where they play a modulatory role in action potential generation [7][8][9]. The channels are also expressed in human alveolar macrophages [10], rat choroid plexus epithelial cells [11], rabbit kidney and colon epithelial cells [12], human gliomas [13], and rat prostate cancer cell lines [14].…”
Section: Introductionmentioning
confidence: 99%